Pengaruh Kemajuan Teknologi, Literasi Keuangan, dan Risk Tolerance Terhadap Minat Investasi Mahasiswa Solo Raya - Yosafat Angga Praditya Nugroho; Putri Maisara (Syntax Idea)
This research has been conducted to college students in Solo and it is useful to see the influence of variable factors of technological progress on investment interests separately, variable factor of financial literacy against investment interest, as well as the influence of risk tolerance on investment interest that have been tested to 107 respondents based on the sampling criteria. The findings of explanation for overall results in this research are free variables from advanced technology, financial literacy, and influental risk of tolerance partially which have positive and significant values toward investment interest, where in this case investment interest is a bound variable factor.